Oyster Biodeposition Alleviates Sediment Nutrient Overload: A Case Study at Shenzhen Bay, China - Mangi, Autif Hussain; Yan, Qi; Song, Xiao; Song, Junting; Lan, Xia; Zhou, Jin; Cai, Zhong-Hua (Frontiers in Microbiology, 2021)
Oysters are ecological engineers, and previous studies have examined their role as competent facilitators of ecological restoration. However, the decisive role of oysters in the aquatic environment is still debatable because oyster biodeposition (OBD) may also increase the nutrients enriched in sediments. In order to better interpret this problem, we sampled sediment cores from representative oyster culture areas and uncultured areas in Shenzhen Bay. The results have shown that the TOC (total organic carbon) and TN (total nitrogen) decreased significant (P<0.05) at the surface sediment layer (0–20 cm deep) and the sediment layer (20–40 cm deep)of the oyster site compared to the reference site. The decreased TOC and TN were also observed at 60 to 100 cm sediment depth in the oyster site. This indicated that the OBD significantly impacted the concentration of TOC and TN in the sediment. To confirm the alleviative role of OBD, we conducted stable isotope (δ13C and δ15N) analyses, which further demonstrated the presence of more heavier and less lighter forms of organic carbon and nitrogen sediment. The surface sediment layer (0–20 cm) at the oyster site showed 8% more δ13C‰ compared to the control site (P<0.05), reflecting the reduction in the TOC. In order to reveal the potential microbial mechanisms involved in OBD, we performed a functional analysis using the Geochip5 advanced microarray technology. Regarding carbon metabolism, we observed that genes (encoding pullulanase, glucoamylase, exoglucanase, cellobiase, and xylanase) involved in the degradation of relatively labile C-based molecules (e.g., starch, cellulose, and hemicellulose) were highly represented in an experimental area (P < 0.05). In addition, microbes in the experimental area exhibited a greater capacity for degrading recalcitrant C (e.g., lignin), which involves glyoxal oxidase (glx), manganese peroxidase (mnp), and phenol oxidase. Among the genes controlling nitrogen metabolism, the genes involved in denitrification, assimilation, ammonification, and nitrification were differentially expressed compared to the control area. These results indicated that microbial metabolic roles might have enhanced the C/N-flux speed and reduced the overall nutrient status. We concluded that OBD alleviates sediment nutrient overload under oyster farming from a microbial ecological perspective in a rapidly urbanized coastal area.